Implementation of Syekh Muhammad Djamil Jaho’s Islamic Education Perspective through Adat and Syara’ Interaction - Januar Januar (Islam Transformatif : Journal of Islamic Studies, 2022)
This study aims to reveal the application of Islamic education from the perspective of Sheikh Muhammad Jamil Jaho through the interaction of adat and syara’. The method used in research is content analysis, with the steps of having a general idea about the research topic, looking for supporting information, clarifying the focus (expanding or narrowing and organizing reading), searching for and finding the material needed, re-organizing and making research notes (at best central), reviewing and re-enriching reading material, re-organizing material or notes and starting to write. The research results show that applying Islamic education from the perspective of Syekh Muhammad Djamil Jaho through the ‘interaction of adat and syara’ is developed through three values: adat and syara’ values, national values, and cultural values. The three elements of value are essential points in the affinity of custom and syara’ of Syekh Muhammad Jamil Jaho, each of which is related and cannot be separated in Minangkabau society, the interaction between religious values, national values and traditional values,which always interact with each other, mediates between one with another. The affinity of adat and syara’ is also inseparable from the authority holders of adat and syara’ values, in its development, it has experienced very problematic developments in terms of terminological definitions and implementation.